Food and Feeding Habits of Nemipterus peronii (Valenciennes) from the South China Sea - Mohd Said, Mohd Zaki; Mohammad Mohsin, Abu Khair; Ambak, Mohd Azmi (Universiti Putra Malaysia Press, 1994)
A study was conducted to investigate the food and feeding habits of Nemipterus peronii from the South China Sea. Diets consisted of fish, Leiognathus elongatus, L. splendens, Upeneus sulphureus, U. vittatus, Nemipterus sp., Trichiurus sp., Selaroides leptolepis and Saurida sp., shrimps, crabs, squids and miscellaneous decomposed organic and inorganic substances. Fish, shrimps and crabs constituted the main diets. The lowest percentage (0%) of empty stomachs was observed in August and highest in December (45%). Shrimps were absent in the stomachs of length class 9.6 to 11.5 cm while squids were absent in the stomachs of length class smaller than 13.5 cm. Relative importance offood items is presented.